The Role of Top Management Team in Company Digital Transformation - Humaira, Novida; Suriadi, Suriadi; Amang, Andi; Mulyadi, Mulyadi; Sudianto, Sudianto (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The success or failure of a company's efforts in achieving its predetermined goals will largely be determined by the ability of the leader. Every organization must have and need a top leader or top manager who must carry out leadership and management activities for the entire organization as a whole. The purpose of this study is to provide information on the importance of the role of top management team in company digital transformation. The research used in this analysis uses theoretical research that will explain the role of top management team in company digital transformation. To support the exploration and development of theories, concepts, and arguments supported by secondary data. The results of the study show that the top management team has a crucial role in the company's digital transformation. The top management team is responsible for providing direction, support, and resources needed to achieve digital transformation goals.